2019
DOI: 10.3390/su11195211
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Data Collection System for Repetitive Concrete Temperature Monitoring in High-Rise Building Construction

Abstract: The systematic collection and management of on-site information in high-rise building construction are important factors in construction management. Recently, wireless sensor network (WSN) technology has been utilized to manage the various tasks involved in high-rise construction efficiently and in a timely manner. However, because of the repeated installation of sensors and repeaters along with the construction progress, the existing WSN technology is ineffective when applied to the temperature management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In terms of results, the authors demonstrated the µPanel efficiency in supporting easy and fast deployment of complex monitoring systems. They affirm that their compact transmission scheme at the smart-phones as well as the push notifications support are the main concepts reinforcing real time clients as similar to the smartphone-based monitoring in [5].…”
Section: Related Workmentioning
confidence: 77%
See 2 more Smart Citations
“…In terms of results, the authors demonstrated the µPanel efficiency in supporting easy and fast deployment of complex monitoring systems. They affirm that their compact transmission scheme at the smart-phones as well as the push notifications support are the main concepts reinforcing real time clients as similar to the smartphone-based monitoring in [5].…”
Section: Related Workmentioning
confidence: 77%
“…These devices are requested to acquire environmental stimuli, including humidity, temperature, light, and vibrations. The sensor nodes are designed for sensing events, communicating data, and aggregating and processing packets in a central location named sink node [5]. Due to these characteristics, the WSNs are used in various fields such as health care, industry, environmental monitoring, and research and development [19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, digital technologies that can be used in construction supervision were investigated through analysis of policy reports and previous research, and the technologies that could be used in reclassified works were selected by reflecting the review opinions of experts who performed FGI. Detailed information on the analysis targets for deriving applicable digital technologies is as follows: (1) policy reports are the most recently released by the MOLIT, the ministry that oversees Korea's construction industry, taking into account the characteristics that they include digital technologies that have been reviewed by the ministry from the past to the present; and (2) previous researches consist of articles presenting digital technologies that can be used in the construction industry and future strategy reports published by various organizations [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Among them, research that presented overlapping technologies was excluded, and the final analysis targets were selected.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, government reports, and future strategy reports, digital technologies applicable to the construction industry have been presented in various categories, such as fully automated construction systems, AI, and BIM [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Among various references, this study set eight references as the analysis target, excluding those that presented overlapping digital technologies [6,14,[25][26][27][28]48,50].…”
Section: Review Of Applicable Digital Technologiesmentioning
confidence: 99%